ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI VOLUME TRANSAKSI PASAR UANG ANTAR BANK DI INDONESIA TAHUN 1983â2007 - Prishardoyo, Bambang; Karsinah, K (Semarang State University, 2010)
The source of Interbank Money Market funds derived from the activities of lending and borrowing of funds between one bank with another bank. In this case, banks with excess funds (surplus units) will lend funds to banks that lack of funds (deficit units) to provide compensation for certain interest rate. Participants in the Interbank Money Market are the commercial banks and development and non-bank financial institutions. Funds used in the Interbank Money Market is a short-term nature of funds, where the loan must be repaid no later than 90 days from the closing of the transaction. Variables that used in this reseacrch are the Indonesian bank loans, interest rates, interbank market, total demand deposits and a dummy variable that is public confidence in the banking, it is concluded that the Indonesian bank loans and money market rates between banks has a positive and significant impact on volume interbank money market transactions. While the amount of demand deposits and public confidence in the banking is not significantly affect its volume of transactions in the interbank money market